2021
DOI: 10.3390/micro1020015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Effects of Native and Anionic Nanofibrillar Cellulose Hydrogels for Full-Thickness Skin Wound Healing

Abstract: Nanofibrillar cellulose (NFC)-derived dressings such as films, hydrogels, and aerogels are one of the favorable materials for wound healing due to their proper mechanical properties and water holding ability. However, the therapeutic differences between native and anionic NFC materials are rarely studied. In this report, we compared the differences and addressed the regenerative potential of native and anionic wood-derived NFC hydrogels for wound treatment. In vitro characteristics of the hydrogels were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Accordingly, we also observed a difference between NFC and aNFC scaffolds in the EV yield and time course, independent of the same culture conditions, which may implicate preferential chemical properties of aNFC or differences in matrix stiffness. Both matrices are nanocellulose, but NFC is a native sugar, while aNFC is anionic (Na + salt – 20% of the hydroxyl groups ionized) (Koivuniemi et al., 2021 ). With shorter and thinner fibres (Sheard et al., 2019 ), aNFC is more viscous than NFC at 0.5% concentration, which may have an impact to, for example, cell proliferation and thereby the EV production.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we also observed a difference between NFC and aNFC scaffolds in the EV yield and time course, independent of the same culture conditions, which may implicate preferential chemical properties of aNFC or differences in matrix stiffness. Both matrices are nanocellulose, but NFC is a native sugar, while aNFC is anionic (Na + salt – 20% of the hydroxyl groups ionized) (Koivuniemi et al., 2021 ). With shorter and thinner fibres (Sheard et al., 2019 ), aNFC is more viscous than NFC at 0.5% concentration, which may have an impact to, for example, cell proliferation and thereby the EV production.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the animal free-origin, NFC hydrogel would be an optimal biomaterial to be utilized in future cell-therapy applications without immunomodulatory effects. In previous studies, both neutrally charged and anionic-charged NFC hydrogel has been shown to provoke a normal inflammatory response in vivo, suggesting a safe-to-use protocol for their application in cell transplantation [ 44 , 45 ]. During culturing in NFC hydrogel, hASCs changed their cell spheroid formation into capillary-like structures, which could be beneficial for angiogenesis protection.…”
Section: Discussionmentioning
confidence: 99%
“…The wound contraction was recorded with a digital camera at determined time within two weeks (figure 9(A)). CA/SA instantly during the treatments, with no adherence to the incision site [49]. In comparison, the CSL solution took 2 min to cure, fill in, and attach to the wound site.…”
Section: In Vivo Wound Healingmentioning
confidence: 99%